Impacto de los programas de bienestar universitario en la calidad de vida de los estudiantes (2020)
The objective of this study is to identify and describe the impact of wellness programs on the quality of life of university students. A retrospective and descriptive bibliometric study was performed; Articles indexed in the Scopus database were reviewed, of which 11 publications were selected to prepare this article, taking into account the title, affiliation of the authors, abstract and conclusions. 81.8% of the students who participated in a university wellness program had a positive impact on their quality of life. In 18.2%, no significant differences were found between students who participated and those who did not participate. Quality of life is a cross-sectional variable in university wellness programs, which makes it necessary to evaluate other factors when establishing an intervention strategy.